TINJAUAN PEMAHAMAN GURU BIOLOGI DALAM MENGHADAPI KURIKULUM 2013 DI SMA NEGERI SE-KOTA PADANG TAHUN PELAJARAN 2014/2015 - Ningsih, Eva Nofria (Pendidikan Biologi, 2014)
This research is motivated by the lack of knowledge and understanding of the biology teachers about curriculum 2013. The aim of this research is to determine the understanding of the biology teachers in SMAN Padang city about curriculum 2013 in academic year 2014/2015. The type of this research is a descriptive research with quantitative method. The sample in this research is 20 biology teachers in SMAN Padang city in 2014/2015. The data obtained by distributing questionnaires to the respondents. The result shows that percentage of biology teachers understanding in SMAN Padang city about 2013 curriculum in academic year 2014/2015 as a whole with an average of 79.05% with a good category. It can be concluded that the understanding of the biology teachers in SMAN Padang city in academic year 2014/2015 about curriculum 2013 is good.